Ultrasound examination in gastric diseases in dogs: description of cases - Mamprim, Maria Jaqueline [UNESP]; Sartor, Raquel; Muller, Thiago Rinaldi [UNESP] (Univ Federal Rural Pernambuco, 2011)
Ultrasound is considered the method of choice for evaluation of the gastrintestinal wall. Thickening of the wall is the most common ultrasonographic finding in gastric disorders. Inflammatory and neoplastic disorders are the most frequent causes of wall thickening. Case report 1: Boxer, with abdominal distension, ultrasound examination detected marked diffuse thickening of the gastric wall with loss of definition of wall layers. Fine needle aspiration guided by ultrasound diagnosed gastric carcinoma. Case report 2: mixed breed dog presenting oliguria, emesis and melena, the ultrasound examination showed diffuse thickening of the gastric wall, but with preserved layers and presence of calcification areas. An inflammatory process of the gastric wall was diagnosed using cytology. The distinction between inflammatory and neoplastic processes is performed based on several factors such as distribution, symmetry, size and architecture of the parietal layer in the lesions, and ultrasonography is a valuable tool to direct diagnosis and treatment.
Keywords: dogs; ultrasound; stomach